2021
DOI: 10.1029/2020gl092354
|View full text |Cite
|
Sign up to set email alerts
|

Role of Groundwater in Sustaining Northern Himalayan Rivers

Abstract: Mountains and highlands serve as "water towers" as they provide downstream alluvial plains and lowlands with freshwater (Viviroli & Weingartner, 2008). The Himalayas are the source of water for all of the major rivers in southeast Asia and play a significant role in supplying freshwater for the vast lowland areas of China, India, Bhutan, Nepal and Pakistan (Bookhagen, 2012;Fan et al., 2019). These Himalayan "water towers" are closely related to human welfare and ecosystem health because of their role in genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 63 publications
(55 reference statements)
0
21
0
Order By: Relevance
“…A better understanding of water storage changes is essential for water resources management to ensure water security and food production (Immerzeel & Bierkens, 2012). Groundwater sustains rivers in winter and buffers droughts to maintain fragile ecosystems, especially in arid or semi‐arid regions (de Graaf et al., 2019; Famiglietti, 2014; Fan et al., 2013; Gleeson et al., 2016; Rodell et al., 2009; Taylor et al., 2013; Yao et al., 2021). Over the past decades, TP has experienced dramatic glacier retreat, permafrost degradation, and lake expansions caused by global warming (Brun et al., 2017; Cheng & Wu, 2007; Feng et al., 2019; Ji et al., 2020; Kuang & Jiao, 2016; Yao et al., 2012, 2022; Yi et al., 2021; Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of water storage changes is essential for water resources management to ensure water security and food production (Immerzeel & Bierkens, 2012). Groundwater sustains rivers in winter and buffers droughts to maintain fragile ecosystems, especially in arid or semi‐arid regions (de Graaf et al., 2019; Famiglietti, 2014; Fan et al., 2013; Gleeson et al., 2016; Rodell et al., 2009; Taylor et al., 2013; Yao et al., 2021). Over the past decades, TP has experienced dramatic glacier retreat, permafrost degradation, and lake expansions caused by global warming (Brun et al., 2017; Cheng & Wu, 2007; Feng et al., 2019; Ji et al., 2020; Kuang & Jiao, 2016; Yao et al., 2012, 2022; Yi et al., 2021; Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This rate was slightly lower than that at Beiluhe Lake (47 mm per month, Huang et al., 2016, 2019) and Nam Co (44 mm per month, B. Wang et al., 2020) because of the lower wind speed and air temperature at Lumajiangdong Co. The surface runoff is very limited and negligible during the ice‐covered period on the TP (Kan et al., 2018; Y. Yao et al., 2021; Zhang, Su, et al., 2013; Zhang, Yao, et al., 2013), which is also confirmed by field expeditions in late September 2020 (Figure S6 in Supporting Information ). Therefore, surface runoff was ignored in water balance calculation for the ice‐covered period.…”
Section: Resultsmentioning
confidence: 92%
“…Groundwater‐flow system on the TP can be conceptualized in three regimes: near‐surface shallow groundwater above permafrost, deeper groundwater below permafrost and groundwater under low‐lying valleys and fault zones (Cheng & Jin, 2013; Ge et al., 2008). Groundwater flow on the TP is usually driven and sustained by the topographic gradient with recharge occurring at high elevations through the infiltration of precipitation and meltwater from snow and ice (Ge et al., 2008; Ma et al., 2021; Y. Yao et al., 2017, 2021). Though limited, studies show that groundwater storage on the TP has increased considerably since the 2000s (Jiao et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The model was further used in the Marmot Creek Research Basin of the Kananaskis River Valley of the Canadian Rockies and focused on the role of cold region processes in hydrology. Yao et al (2021) used MODFLOW-NWT to evaluate the annual and seasonal contributions of groundwater discharge to total river flow in the Yarlung Zangbo basin on the northern Himalayan mountainous region. Results indicated that the groundwater recharge and discharge would increase with projected increasing ratio of recharge to precipitation, and thawing permafrost would increase groundwater recharge and discharge.…”
Section: Watershed Scalementioning
confidence: 99%